Research Mapping on Takaful Performance - Irni Nuraini (Tamkin Journal, 2023)
This study aims to examine research patterns concerning Takaful Performance. The studied data came from the Scopus database, which was accessed on March 6, 2023. A total of 62 papers were retrieved. The data were analyzed with the Rstudio Bibliometrix program and biblioshiny tools to determine the research advancements on the Takaful Performance. The data demonstrates that the development of Takaful Performance research began in 2009 and has accelerated since 2015. Nazri and Omar are the most productive writer on this subject. Takaful, Malaysia, and Efficiency are the most commonly occurring keywords. According to the themes in the Takaful Performance study that has the potential to be expanded, this research has a great deal of room for growth.